Solution approaches for the soft drink integrated production lot sizing and scheduling problem - Ferreira, Deisemara; Morabito, Reinaldo; Rangel, Socorro (Elsevier B.V., 2009)
In this paper we present a mixed integer programming model that integrates production lot sizing and scheduling decisions of beverage plants with sequence-dependent setup costs and times. The model considers that the industrial process produces soft drink bottles in different flavours and sizes, and it is carried out in two production stages: liquid preparation (stage I) and bottling (stage II). The model also takes into account that the production bottleneck may alternate between stages I and II, and a synchronisation of the production between these stages is required. A relaxation approach and several strategies of the relax-and-fix heuristic are proposed to solve the model. Computational tests with instances generated based on real data from a Brazilian soft drink plant are also presented. The results show that the solution approaches are capable of producing better solutions than those used by the company. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Lot sizing; Scheduling; Soft drink industry; Mixed integer programming; Relax-and-fix heuristic